2022
DOI: 10.1039/d1ma00957e
|View full text |Cite
|
Sign up to set email alerts
|

Poly(l-lactide): optimization of melting temperature and melting enthalpy and a comparison of linear and cyclic species

Abstract: Experiments are performed to obtain the highest Tm and ΔHm values for poly(l-lactide)s. They also include comparison with literature data and of cyclic and linear species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…who determined that the length of 10 repeat units (lactyl units) in the 10 3 ‐helical conformation of the α ‐modification of PLA amounts to 2.89 nm. [ 45 ] Annealed cPLA typically have crystal thicknesses ( l c ) in the range of 20–28 nm, [ 35,38 ] and the values recorded for the SnBiph catalyzed samples listed in Table 1 fall into this range. For example, a crystal thickness of 25 nm corresponds to chain segment of ≈85 repeat units, including two loops with together 8 units.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…who determined that the length of 10 repeat units (lactyl units) in the 10 3 ‐helical conformation of the α ‐modification of PLA amounts to 2.89 nm. [ 45 ] Annealed cPLA typically have crystal thicknesses ( l c ) in the range of 20–28 nm, [ 35,38 ] and the values recorded for the SnBiph catalyzed samples listed in Table 1 fall into this range. For example, a crystal thickness of 25 nm corresponds to chain segment of ≈85 repeat units, including two loops with together 8 units.…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis and characterization of cPLA have rapidly increased over the past 15 years. [ 7–40 ] The polymerization methods may be subdivided into two categories, first, polymerizations obeying the ROPPOC definition, meaning ring‐opening polymerization with simultaneous polycondensation (including cyclization), [ 41 ] and second, ring‐expansion polymerization (REP) using covalent cyclic catalysts. [ 42 ] The present work is based on REPs catalyzed by two cyclic tin compounds, 2,2‐dibutyl‐2‐stanna‐1,3‐dithiolane (DSTL) and 2‐stanna‐1.3‐dioxa‐4,5,6,7‐dibenzazepine (SnBiph, see Scheme ), because these catalysts have proven in recent REPs conducted in bulk, that they may yield medium and high molecular weight cPLA with average number molecular weights ( M n ) up to 200 000 and average weight molecular weights ( Mw ) up to 400 000) along with extraordinarily high melting temperatures ( T m ) and melting enthalpies (Δ H m ).…”
Section: Introductionmentioning
confidence: 99%
“…The temperature transitions of the PLC copolymer were investigated by differential scanning calorimetry (DSC). Since these properties, that is, glass transition temperature ( T g ), crystallization temperature ( T c ), melting temperature ( T m ), enthalpy of melting (Δ H m ), and percentage crystallinity, as a results from the varying of the copolymer composition, monomer sequencing, and molecular weight, are responsible for its performance in desired applications 50 …”
Section: Resultsmentioning
confidence: 99%
“…Since these properties, that is, glass transition temperature (T g ), crystallization temperature (T c ), melting temperature (T m ), enthalpy of melting (ΔH m ), and percentage crystallinity, as a results from the varying of the copolymer composition, monomer sequencing, and molecular weight, are responsible for its performance in desired applications. 50 Differential scanning calorimetry (DSC) thermograms of the PLC copolymer with different heating rate of 5, 10, 20, and 50 C min À1 are as shown in Figure 4. It can be seen that no transition temperature was observed in the first heating scan of the untreated PLC at different rate as shown in Figure 4a.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 99%
“…In two previous papers it was demonstrated that when the first recrystallization of the PURC L-lactide used for this and previous studies is optimized, the second recrystallization does not enhance the molecular weights. [27,28]…”
Section: Polymerizations At 160 °Cmentioning
confidence: 99%